2011
DOI: 10.1007/s13238-011-1016-3
|View full text |Cite
|
Sign up to set email alerts
|

Animal models for the atherosclerosis research: a review

Abstract: Atherosclerosis is a leading cause of death worldwide, and its mechanisms are still unclear. However, various animal models have significantly advanced our understanding of the mechanisms involved in atherosclerosis and have allowed the evaluation of therapeutic options. The aim of this paper is to review those animal models (i.e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 110 publications
0
94
0
3
Order By: Relevance
“…In our previous study, we found that Endostar could inhibit neovascularization and plaque growth in the rabbit model of AS 23) . However, vasa vasorum in rabbits or mice is thinner than in porcine and human arteries 37) . In this swine model of AS, we found that the density of vasa vasorum and IMT in the AS Endostar group was markedly less than that in the AS group.…”
mentioning
confidence: 90%
“…In our previous study, we found that Endostar could inhibit neovascularization and plaque growth in the rabbit model of AS 23) . However, vasa vasorum in rabbits or mice is thinner than in porcine and human arteries 37) . In this swine model of AS, we found that the density of vasa vasorum and IMT in the AS Endostar group was markedly less than that in the AS group.…”
mentioning
confidence: 90%
“…Since then, a number of animal models have been used to explain the relationship between disorders of lipid metabolism and atherogenesis (see reviews [108,109]). In this sense, dietary lipid manipulation and use of naturally defective animals, such as Watanabe heritable hyperlipidemia (WHHL) rabbits, have been the focus of most experimental settings (see chapter 22).…”
Section: The Rabbit Modelsmentioning
confidence: 99%
“…2011). Several disease specific knockout and transgenic mouse models are also used, for instance, to study cardiovascular drugs (Avila MD, 2011;Xiangdong L, 2011;Zaragoza C, 2011) and autoimmune disease targeting agents (Gulinello M, 2011;Schroeder MA, 2011). Immunodeficient animals, such as nude, SCID and SCID/NOD tumor xenograft mouse models, are also important for testing and development of new chemotherapeutic drugs (Sausville EA, 2006;Khan N, 2009;Umar A, 2010;Baiocchi M, 2010).…”
Section: Importance Of Preclinical In Vivo Modelsmentioning
confidence: 99%